HDL-cholesterol levels and risk of age-related macular degeneration: a multiethnic genetic study using Mendelian randomization. (12th September 2017) - Fan, Qiao; Maranville, Joseph C; Fritsche, Lars; Sim, Xueling; Cheung, Chui Ming Gemmy; Chen, Li Jia; Gorski, Mathias; Yamashiro, Kenji; Ahn, Jeeyun; Laude, Augustinus; Dorajoo, Rajkumar; Lim, Tock Han; et al.
Abstract: Background: Dyslipidemia, particularly high-density lipoprotein cholesterol (HDL-C), has recently been implicated in the pathogenesis of age-related macular degeneration (AMD), the leading cause of vision loss. However, epidemiological studies have yielded conflicting results. Methods: We investigated the causal role of plasma lipid levels in AMD in multiethnic populations comprising 16 144 advanced AMD cases and 17 832 controls of European descent, together with 2219 cases and 5275 controls of Asian descent, using Mendelian randomization in three models. Model 1 is a conventional meta-analysis which does not account for pleiotropy of instrumental variable (IV) effects. Model 2 is a univariate, inverse variance weighted regression analysis that accounts for potential unbalanced pleiotropy using MR-Egger method. Finally, Model 3 is a multivariate regression analysis that addresses pleiotropy by MR-Egger method and by adjusting for effects on other lipid traits. Results: A 1 standard deviation (SD) higher HDL-cholesterol level was associated with an odds ratio (OR) for AMD of 1.17 (95% confidence interval: 1.07–1.29) in Europeans ( P = 6.88 × 10 –4 ) and of 1.58 (1.24–2.00) in Asians ( P = 2.92 × 10 –4 ) in Model 3. The corresponding OR estimates were 1.30 (1.09–1.55) in Europeans ( P = 3.18 × 10 –3 ) and 1.42 (1.11—1.80) in Asians ( P = 4.42 × 10 –3 ) in Model 1, and 1.21 (1.11–1.31) in Europeans ( P = 3.12 × 10 –5 ) and 1.51 (1.20–1.91) in Asians ( P = 7.61 × 10 –4 ) in Model 2. Conversely, neither LDL-C (Europeans: OR = 0.96, P = 0.272; Asians: OR = 1.02, P = 0.874; Model 3) nor triglyceride levels (Europeans: OR = 0.91, P = 0.102; Asians: OR = 1.06, P = 0.613) were associated with AMD. We also assessed the association between lipid levels and polypoidal choroidal vasculopathy (PCV) in Asians, a subtype of AMD, and found a similar trend for association of PCV with HDL-C levels. Conclusions: Our study shows that high levels of plasma HDL-C are causally associated with an increased risk for advanced AMD in European and Asian populations, implying that strategies reducing HDL-C levels may be useful to prevent and treat AMD.